Cetaceans 4th Grade Curriculum - Maia Patterson McGuire; Ruth Francis-Floyd (EDIS)
This new curriculum provides a series of individual lessons covering cetacean (whale and dolphin) biology and ecology. The curriculum uses charismatic megafauna to engage students and inspire them to want to learn more. Lessons highlight some of the ways that humans impact and can protect cetaceans. They help teachers address science, mathematics, language arts, or visual arts objectives and could be used in place of current lesson plans for many topics. Sunshine State Standards and Common Core correlations are provided. Written by Maia Patterson McGuire and Ruth Francis-Floyd, and published by the UF/IFAS Veterinary Medicine—Large Animal Clinical Sciences Department, June 2019.